¿Qué lugar ocupan actores sociales en el contexto de servicios ecosistémicos? Una revisión en áreas de ecología y biología de la conservación - del castillo, Daniela; di Pasquo, Federico Martín; Busan, Tomás Emilio; Klier, Gabriela; Mahler, Bettina (Sustainability in Debate, 2019)
Ecosystem Services (ES) are a tool used to address environmental issues. The assessment of ES in ecological, monetary or sociocultural terms is a key element of this perspective. We conducted a review of scientific articles focused on SE published between 2005-2017, investigating the way in which articles recover voices from different social actors (SA). In general, local SA were not included in the objectives, nor did they participate in research. The articles rarely addressed conflicts between different SA. When local SA performed sociocultural valuation, researchers generally selected ES to be assessed. Considering that the conflicts linked to SE are immersed in complex social contexts, with SA presenting different lifstyles, neglecting "social dimensions" can lead to leave aside cultural distances, differences of class, geographical location, and this can lead to the development of management options that are unfeasible or even harmful to the actors involved.